Muslims in the Russian army - Davies, Franziska, author. Link
1 online resource.
Keywords: "Muslims in the Russian Army is the first comprehensive account of the tsarist army's relationship to Muslim soldiers in late imperial Russia. When Russia mobilized her army in the summer of 1914 more than half a million of the soldiers recruited for the front were Muslims from the Volga-Ural region, that is present-day Tatarstan and Bashkortostan. They were the only ones among the millions of Muslim subjects of the tsar who were recruited into the regular army, in spite of the fact that universal liability to military service had been introduced in the Russian Empire in 1874. But in practice, special regulations had been adopted for the Crimean Tatars, while the Muslim subjects of Central Asia and the Caucasus remained exempted, revealing the limited ability of the imperial state to extend the "Great Reforms" under Alexander II to its colonial peripheries. The book highlights the empire's policies of accommodating the religious needs of Muslim soldiers in the army, but argues that this should be understood as a form of colonial accommodation and not as an embrace of tolerance as has been done before. By reconstructing not only the perspectives of military and bureaucratic elites and the Muslim intelligentsia, but also considering accounts written by Muslim soldiers this book includes the voices of the colonized whose stories are still too often ignored in the historiography of the Russian Empire. This book is a valuable contribution to contributes to three much-debated fields of imperial and colonial history: the accommodation of religious and ethnic diversity, the impact of the state's modernization projects, and the perception of imperial institutions by non-Russian subjects. It will be of interest to researchers in European History, Modern History, Military and Naval History, and Central Asian, Russian and Eastern European Studies"--